Increasing access to self-managed abortion through pharmacies: programmatic results and lessons from a pilot program in Oromia, Ethiopia - Chekol, Bekalu Mossie; Belai Mehari, Abiyot; Rezene, Blain; Muluye, Samuel; Ayana, Yadeta; Sisay, Elsabet; Dijkerman, Sally; Assefa, Genene (Frontiers in Reproductive Health, 2025)
Despite increased availability of safe abortion following legal reform in Ethiopia, one-half of public sector abortion services are treatment of postabortion complications, indicating challenges meeting women's needs. Self-managed abortion (SMA)—the ability of pregnant people to manage their unwanted pregnancies with or without the support of a health care provider—is a safe, feasible, and acceptable option for women at gestational ages up to 12 weeks. Seeing the potential of SMA to vastly expand access to safe abortion and reduce postabortion complications, a pilot initiative targeting private pharmacies was implemented by the Ethiopian Ministry of Health, the Oromia Regional Health Bureau, and a non-profit organization. From December 2021 to March 2023, implementers trained and supported 41 pharmacies to provide SMA counseling and medical abortion drugs, with and without prescriptions, which was considered to contradict the legal framework at the time. Pharmacy clients' SMA experiences were documented in logbooks and via 21-day follow-up phone surveys. Thirty-two pharmacies (78%) supported 1,457 self-managed abortions during the pilot. Among clients with complete follow-up surveys (n = 1,233), 98.3% had a complete abortion without needing additional treatment. Only four clients (0.3%) reported a complication. The pilot demonstrated high demand for and feasibility of increasing access to quality SMA through private pharmacies in Ethiopia, but challenges remain due to the lack of a legal framework. We recommend providing multi-sector support on SMA to private pharmacies so they can in turn improve safe abortion accessibility by bringing safe, acceptable services closer to the people that need them.